The concept of criminal policy in corruption effort criminal acts of narcotics abuse based restorative justice - Bastianto Nugroho; Arif Darmawan; Otto Yudianto; Erny Herlin Setyorini (Technium Social Sciences Journal, 2021)
This research is a normative research, which examines the study of documents using legal materials such as laws and legal theory. In the history of narcotics during human civilization, at first it’s purpose was for treatment in the world of health. In the times, it’s not only for medicine but has been misused for the purpose of getting pleasure which ultimately makes human productivity decline. Therefore, the illegal distribution and use of narcotics is finally prohibited. The State of Indonesia to achieve legal goals in accordance with Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia states “All citizens have the same position in law and government, must uphold the law and government without exception”. In this way, every attitude, policy, and behavior of state apparatus and residents (citizens and foreigners) must be based on and in accordance with the law.